Peningkatan Soft Skill Siswa Melalui Pembuatan Sabun Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) di MA. Habiburrahman Jatian - Pakusari Jember - Hadi Barru Hakam Fajar Siddiq; Agnis Pondinekaria Aditama (Warta Pengabdian, 2018)
Community service activities undertaken by lecturers from Pharmacy Diploma III Program of Pharmacy Academy of Jember held on March, 2018, held at MA. Habiburrahman Jatian, Pakusari Jember provides benefits for students in improving students skill through soap red dragon fruit extract. MA. Habiburrahman was senior high school under the Ministry of Religious Affairs located in Jatian-Pakusari-Jember. MA. Habibirrahman also has a religious education institution that is Pondok Pesantren Habibirrahman. Nearly 70% of students of MA. Habiburrahman were santri. The results show that MA Habiburrahaman does not have a curculum that focuses on the attachment of students. Therefore, this program provides many benefits to students to add soft skills in the field of technology. In addition, this program is in great demand by all students. Keywoard: Community Servive, Soft Skill, Soap, Red Dragon Fruit